Penentuan Ukuran Sumur Resapan Berdasarkan Luasan Rumah, Curah Hujan, dan Infiltrasi (Studi Kasus di Komplek Perumahan Reni Jaya, Pamulang, Tangerang, Banten) - Susanto, Agus; Suhardianto, Anang (Jurnal Matematika Sains dan Teknologi, 2005)
All developers should consider continuity of water supply for the house dweller, as much rain water falling on the house yard will be lost as run-off water instead of filling the shallow ground water. Hence, there should be absorption wells to absorb the water falling from house roof. By so doing, it can increase ground water supply.  However, there should be an exact dimension of the absorption well, as the amount of the falling water from house roof depends on the roof width. The dimension of the well for each house can be measured based on roof width, rain fall, and soil capability to absorb water or infiltration capability. For unrennovated house, well diameter are 80 to  120 cm and its total depth are 60 to 160 cm. While for rennovated house, well diameter are 90 to 140 cm and total depth are 120 to 190 cm